ANALISIS PENGARUH KEPEMIMPINAN DAN KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN - Deni Wardani; Farrah Fauzia Jacub (Indonesia Banking School, 2015)
This research aimed to prove that leadership and compensation influence on job satisfaction at PT Pertamina Lubricants. Within this research, population research refers to employee at PT Pertamina Lubricants which is about 80 employees that already pass the probation time. Sample used about 30 respondents and data was taken by way of questionnaires.The data collection is analyzed by Regression Analysis. The result of this analysis showed that Y= 3,474 +0,321X1+0,718X2, and the determination coefficients is about 50,1%. Byt that means, there are signification effect about Leadership and Compensation on Job Satisfaction.Keywords: Leadership, Compensation, Job Satisfaction, Employees